2017
DOI: 10.3390/molecules22091407
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Silver Nanoparticles on Orthodontic Elastomeric Modules: Evaluation of Mechanical and Antibacterial Properties

Abstract: In the present study, silver nanoparticles (AgNPs) were synthesized in situ on orthodontic elastomeric modules (OEM) using silver nitrate salts as metal-ion precursors and extract of the plant Hetheroteca inuloides (H. inuloides) as bioreductant via a simple and eco-friendly method. The synthesized AgNPs were characterized by UV-visible spectroscopy; scanning electron microscopy-energy-dispersive spectroscopy (SEM-EDS) and transmission electron microscopy (TEM). The surface plasmon resonance peak found at 472 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 68 publications
1
48
0
Order By: Relevance
“…According to the characterization of AgNPs, it is very well known that particles with zeta potential values between +30 and −30 mV are considered a stable suspension limiting the agglomeration [25,26]. It has been reported that the concentration of AgNO 3 (0.01, 0.1, and 0.5 M) can affect the size of silver nanoparticles (20,25, and 11 nm) and the zeta potential values (−26.37, −37.95, and −28.23, resp. ); moreover, the pH values in the solution could also promote a high risk of agglomeration when pH values < 7 were used, while pH values > 7 could have better conditions for nonagglomerated particles [26].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the characterization of AgNPs, it is very well known that particles with zeta potential values between +30 and −30 mV are considered a stable suspension limiting the agglomeration [25,26]. It has been reported that the concentration of AgNO 3 (0.01, 0.1, and 0.5 M) can affect the size of silver nanoparticles (20,25, and 11 nm) and the zeta potential values (−26.37, −37.95, and −28.23, resp. ); moreover, the pH values in the solution could also promote a high risk of agglomeration when pH values < 7 were used, while pH values > 7 could have better conditions for nonagglomerated particles [26].…”
Section: Discussionmentioning
confidence: 99%
“…7 Journal of Nanomaterials elastomeric modules could potentially combat the dental biofilm decreasing the incidence of dental enamel demineralization during the orthodontic treatments [20]. Other study evaluated, through an in vivo experimental design, the antimicrobial activity on S. mutans bacteria and the ion release capacity of nanosilver-coated orthodontic brackets; these authors concluded that AgNP-coated brackets could significantly help to decrease the presence of spot lesions during fixed orthodontic treatments, even may have a potential solution for systemic compromised patients such as immune deficiency, diabetics, and subacute bacterial endocarditis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The applications of these nanomaterials are diverse in the chemical industry, in electronics, and even in medicine [1,2]. One of the main applications of nanomaterials, however, is in catalysis.…”
Section: Introductionmentioning
confidence: 99%